Choice of Timber Species for Plantation on the Basis of Utilisation Parameters - Kothiyal, V.; Bhandari, R.; Jain, V. K. (Indian Forester, 2005)
Many wood species have been planted under social forestry/agroforestry programmes in the country in the last few years with a view mainly to increase green cover and meet the local needs for timber, fodder and food etc. However available scientific data on the utilization aspects of harvested timber appears to have remained in the back seat while selecting timber species for plantation. This resulted in production of timbers which were either marginally suitable for utilisation of various wood products or required development of the suitable processing technology before being put to use. This paper focuses on the need for adopting a holistic approach while choosing timber species for plantation on the basis of scientific input from various angles. Natural durability and treatibility (ease of treatment with preservative) is the foremost requirement for utilization of solid timber for any given end use such as in agricultural implements, furniture, rural housing and construction etc. The second requirement is the physical and mechanical properties of timbers, which ultimately determine its suitability for the desired end use/industrial application. The timbers with multi-utility can be given tbe next importance. Plantation timber species have been grouped based on the above parameters, It is suggested that these requirements coupled with growth paratpeters in different agro climatic zones may be used for prioritizing the species for plantation. It is suggested that the species placed in the higher group may be given preference to that in the lower groups for maximum benefit to the society.